A Financial Feasibility Study of New Product Line Healthy Children Food Business: Case Study of Lil'bites - Tantuayo, Fairuuz Fawwas Alfarizi; Afgani, Kurnia Fajar (Journal Integration of Management Studies, 2024)
Based on data from the Indonesian Nutrition Status Survey (SSGI) in 2022, 21.6% of Indonesian children suffer from wasting 7.7%. A disorder known as "wasting" in children occurs when their weight falls till it is higher than what is considered normal for their age. For children's growth and well-being, they must consume enough fruits. Although fruits provide vital vitamins and minerals that boost immunity and general health, many kids dislike them because of their flavor, texture, or inexperience with new meals. Lil'Bites, a startup focusing on children's health, sees this opportunity to create kid-friendly fruit jams as a viable approach to ensuring kids consume enough fruits. This research aims to assess the financial feasibility of developing a new product line, which is a healthy jam for kids, using a quantitative approach, utilizing company data as primary data and data from similar companies as secondary data. The study will evaluate the payback period, net present value (NPV), and internal rate of return (IRR) and assess risk through sensitivity analysis. The results based on the base scenario indicate that the Lil'Bites new product line project is financially feasible, resulting in a payback period of 1.9 years, an NPV of IDR401,807,628, and an IRR of 54.94%, which is significantly higher than the WACC of 9.36%.